2019
DOI: 10.3390/molecules25010095
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial Activity of Lavender Essential Oil Alone and In Combination with Octenidine Dihydrochloride against MRSA Strains

Abstract: In the post-antibiotic era the issue of bacterial resistance refers not only to antibiotics themselves but also to common antiseptics like octenidine dihydrochloride (OCT). This appears as an emerging challenge in terms of preventing staphylococcal infections, which are both potentially severe and easy to transfer horizontally. Essential oils have shown synergisms both with antibiotics and antiseptics. Therefore the aim of this study was to investigate the impact of lavender essential oil (LEO) on OCT efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 41 publications
(58 reference statements)
2
58
1
1
Order By: Relevance
“…Interestingly, at 1220 cm −1 and 1080 cm −1 , the higher intensity in MRSA isolates (with high-level methicillin (MIC = 1000 ± 0.0 mg/L) and penicillin G (MIC ≥ 31.3 ± 0.0 mg/L) resistance strains) can be attributed to the symmetric and asymmetric PO 2 − stretching vibrations in phosphodiester groups, present, among others, in teichoic acid/lipoteichoic acid of Gram-positive bacteria [ 31 ]. The above-mentioned changes may affect the electrostatic interactions with antibacterial molecules, as also proven in our previous studies [ 11 , 13 ]. Moreover, blaR1 protein (which is involved in sensing of the β-lactam antibiotics and then transduction of the information to the cell’s interior) may play an important role in the association with -OH groups [ 32 ].…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…Interestingly, at 1220 cm −1 and 1080 cm −1 , the higher intensity in MRSA isolates (with high-level methicillin (MIC = 1000 ± 0.0 mg/L) and penicillin G (MIC ≥ 31.3 ± 0.0 mg/L) resistance strains) can be attributed to the symmetric and asymmetric PO 2 − stretching vibrations in phosphodiester groups, present, among others, in teichoic acid/lipoteichoic acid of Gram-positive bacteria [ 31 ]. The above-mentioned changes may affect the electrostatic interactions with antibacterial molecules, as also proven in our previous studies [ 11 , 13 ]. Moreover, blaR1 protein (which is involved in sensing of the β-lactam antibiotics and then transduction of the information to the cell’s interior) may play an important role in the association with -OH groups [ 32 ].…”
Section: Discussionsupporting
confidence: 60%
“…Nevertheless, LEO is recommended for the treatment of many skin infections caused by S. aureus such as carbuncles, abscesses, and wounds [ 27 ]. Moreover, our other previous studies showed synergism between LEO and octenidine dihydrochloride against MRSA strains [ 13 ]. Taking that fact into account, linalyl acetate was chosen for the current study.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations